Pelatihan Integrasi Hots Dalam Pengembangan Modul Ajar Kurikulum Merdeka Pada Kelompok Kerja Guru (KKG) Gugus I Sekolah Dasar di Kecamatan Tamiang Hulu Kabupaten Aceh Tamiang - Evi Purnama Bayu Ningsih (Jurnal Kabar Masyarakat, 2023)
This Community Service Activity aims to provide training for the development of independent curriculum teaching modules to improve HOTS thingking skills teachers because there still many challenges for teachers, especially for elementary school teachers related to the independent curriculum. The method applied: (1) counseling, the techniques used in this counseling are lectures, questions and answers, and discussing training materials for the preparation the module, (2) training, the techniques used in the training are observing the model, guiding, and accompanying the teacher when practicing compiling the module according to the assigned task, (3) demonstration, the techniques used in the demonstration are presentation, simulation, and reflecting on training activities. The result of the activity are the increased professionalism of teachers in preparing learning tools and understanding of the independent curriculum learning system reflected through the achievement of counseling activities and assistance in the preparation of teaching modules.